The The Relationship Between Sexual Satisfaction and Husband's Infidelity Intentions - Asniar Khumas; Nur Amalia Muhlisa; Dian Novita Siswanti (ARRUS Journal of Social Sciences and Humanities, 2023)
There are many things that influence marital satisfaction. One of the factors is loyalty to the partner. Therefore, efforts are needed to prevent infidelity to maintain marriage. The purpose of this study was to determine the relationship between sexual satisfaction with the husband's intention of infidelity. The method used is a quantitative method in the form of a survey. Respondents in this study were men who were husbands with a minimum age of 5 years of marriage and domiciled in Makassar City. A total of 100 respondents participated in this study. Data was collected using a sexual satisfaction scale and an infidelity intention scale. The data analysis used is product-moment correlation . The results of the hypothesis test showed a correlation value of r = -0.769 with a significance value of p = 0.000 (p <0.005), which means that there is a significant relationship between sexual satisfaction and the intention of cheating on a husband. A negative correlation value indicates a negative relationship between the intention of infidelity and sexual satisfaction in the husband. This means that the higher the sexual satisfaction, the lower the intention of infidelity. Conversely, the lower the husband's sexual satisfaction, the higher the intention of infidelity. The findings in this study have implications for married couples, especially wives, to pay more attention to sexual satisfaction in their marriage to maintain the quality of their marriage.